2013
DOI: 10.1007/s11661-013-1688-9
|View full text |Cite
|
Sign up to set email alerts
|

The Residual Stress Relaxation Behavior of Weldments During Cyclic Loading

Abstract: Accurate measurement of residual stress is necessary to obtain reliable predictions of fatigue lifetime and enable estimation of time-to-facture for any given stress level. In this article, relaxation of welding residual stresses as a function of cyclic loading was documented on three common steels: AISI 1008, ASTM A572, and AISI 4142. Welded specimens were subjected to cyclic bending (R = 0.1) at different applied stresses, and the residual stress relaxation existing near the welds was measured as a function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 34 publications
(48 reference statements)
1
26
0
Order By: Relevance
“…In general, the following observations can be made for both simulation and actual measurements: (1) there is only a minor change of residual stress when the cut is outside the HTZ; (2) relaxation of stress only becomes significant after the cut reaches the HTZ. The relaxation of the highest stress (R) is defined as [9],…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the following observations can be made for both simulation and actual measurements: (1) there is only a minor change of residual stress when the cut is outside the HTZ; (2) relaxation of stress only becomes significant after the cut reaches the HTZ. The relaxation of the highest stress (R) is defined as [9],…”
Section: Discussionmentioning
confidence: 99%
“…welding, machining, hardening, casting and forging, can all produce residual stresses in the final product. [6][7][8] Thus, good knowledge of the residual stress profile will lead to more accurate fatigue life prediction [9] and allow the optimization of the welding process parameters.…”
Section: Introductionmentioning
confidence: 99%
“…It is well know that the compressive residual stresses induced by shot peening are progressively reduced during the fatigue test, especially in the course of the first cycles. Many factors are involved in this relaxation process, like the induced surface defects (Ref 34), the mechanical properties of the steel, the load applied in the fatigue test and the number of cycles (Ref [35][36][37], as well as the temperature (Ref 38, 39). So, it is important to consider that the compressive residual stresses induced by shot peening will change in the course of the fatigue test, and their final value will depend on the aforementioned variables.…”
Section: Residual Stress Profilesmentioning
confidence: 99%
“…However, tensile residual stresses play a detrimental role on the fatigue performance of structures because of the superimposition of the tensile and cyclic stresses . Moreover, the residual stresses were reported to diminish considerably after the first or initial few loading cycles . Wang et al who indicated that the plastic strain in the same direction as the cyclic loading, played a decisive role on residual stress relaxation.…”
Section: Introductionmentioning
confidence: 99%